Anti-Photoagaing and Photo-Protective Compounds from Marine Organisms - Kim, Se-Kwon (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue Book ""Anti-Photoagaing and Photo-Protective Compounds from Marine Organisms"" is aimed at collecting literature on the below-mentioned keyword topics, which can significantly increase our basic understanding of marine-derived compounds in cosmeceutical product development and increases the value of marine products at the industrial level.